A systematic review on the clinical studies of Remdesivir for COVID-19 in selected Asian countries - Joseph Mari Baguilod Querequincia, Erwin Martinez Faller (Journal of Applied Pharmaceutical Science, 2022)
The focal purpose of this review article is to provide ample information on the different clinical studies conducted in some countries in the Asian region on the utilization of the antiviral drug, Remdesivir, for coronavirus disease 2019 (COVID-19). COVID-19 is caused by severe acute respiratory syndrome coronavirus 2 and has spread in most countries in 2020. Common symptoms of this disease include fever, cough, fatigue, and diarrhea. Certain medicinal agents are being studied to treat COVID-19. One of these medicinal agents is Remdesivir, which is an antiviral agent that is an adenosine nucleotide, which could impede the viral RNA polymerase enzyme. There were countries in the regions of Asia that conducted clinical studies on the use of Remdesivir as an antiviral therapy for COVID-19 infections. Asian countries such as Japan and South Korea permitted the employment of it as a medicinal agent for COVID-19 disease. In other countries in the region, Remdesivir is on phase 3 clinical trial. Doses of 100–200 mg/kg intravenous route could improve clinical outcomes of patients infected with COVID-19 in clinical trial settings. Thus, Remdesivir is a potential antiviral commodity that can be used to treat COVID-19 infections and opted to be wholly established.
Keywords: Remdesivir, COVID-19, antiviral, intravenous, clinical studies, Asian countries